2009
DOI: 10.1139/h09-110
|View full text |Cite
|
Sign up to set email alerts
|

Slow postmeal walking reduces postprandial glycemia in middle-aged women

Abstract: Postprandial blood glucose concentration is a risk factor for the development of cardiovascular diseases and diabetes, even at states well below hyperglycemic levels. A previous study has shown that postmeal exercise of moderate intensity blunts the blood glucose increase after carbohydrate intake (Høstmark et al. Prev. Med. 42(5): 369-371). The objective of the present study was to examine whether even postmeal slow walking would have a similar effect. Fourteen healthy women aged >50 years participated in 3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 20 publications
5
62
4
2
Order By: Relevance
“…48 Exercise plus insulin has an additive effect to some degree in the facilitation of glucose uptake by muscle cells. Previous research has shown that cycling (30 minutes at 70% maximum heart rate) blunts the BG spike after consumption of cornflakes (1 gm carbohydrate per kg body weight), 53 and another study 54 indicated that slow post-meal walking reduced the BG response to a meal of cornflakes (1 gm carbohydrate per kg body weight).Recent research determined that 30 min of light exercise (walking) reduced the blood glucose spike following consumption of a Milky Way candy bar, a typical snack, compared to the spike in BG that occurred when subjects sat after consuming the candy bar. 52 The aforementioned studies were conducted with healthy subjects.…”
Section: Mitigating the Glycemic Effect Of Food With Exer-cisementioning
confidence: 88%
See 1 more Smart Citation
“…48 Exercise plus insulin has an additive effect to some degree in the facilitation of glucose uptake by muscle cells. Previous research has shown that cycling (30 minutes at 70% maximum heart rate) blunts the BG spike after consumption of cornflakes (1 gm carbohydrate per kg body weight), 53 and another study 54 indicated that slow post-meal walking reduced the BG response to a meal of cornflakes (1 gm carbohydrate per kg body weight).Recent research determined that 30 min of light exercise (walking) reduced the blood glucose spike following consumption of a Milky Way candy bar, a typical snack, compared to the spike in BG that occurred when subjects sat after consuming the candy bar. 52 The aforementioned studies were conducted with healthy subjects.…”
Section: Mitigating the Glycemic Effect Of Food With Exer-cisementioning
confidence: 88%
“…50 However, compliance with current exercise recommendations is poor, with self-reported compliance rates of about 35% for those with T2DM. 51 Emerging evidence [52][53][54][55][56][57][58][59] suggests that a short bout of post-meal exercise in particular can attenuate the spike in BG after consumption of carbohydrates, which may be advantageous for those with and without diabetes, including those with dementia. Knowing that a short bout of exercise after consumption of a carbohydrate load could specifically decrease the spike in BG after carbohydrate consumption may be more motivating for compliance than exercising for general improvements in glycemic control.…”
Section: -47mentioning
confidence: 99%
“…Pregnant women should be encouraged to participate in daily activity if they have no contraindications (63 ). Cardiovascular exercise such as walking, if done after meals, is a means to control the postprandial increase in glucose, though it has not been studied in the setting of diabetes in pregnancy (69 ).…”
Section: Intrapartum Management Diet and Pharmaceutical Therapymentioning
confidence: 99%
“…To address this, some investigators have recently assessed the efficacy of low or moderate-intensity exercise protocols (walking) in mitigating metabolic risk factors. Nygaard et al (2009) investigated the effects of a 15-minute or 40-minute postmeal walk on blood glucose levels in 14 older (>50 years) healthy women. The walking was performed at a self-selected slow pace, corresponding to a rating of perceived exertion (RPE) of 9 on the 6-20 Borg scale.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that both walks were effective in significantly lowering average glucose concentration values, and the 40-minute walk significantly lowered glucose incremental area under the curve (iAUC) by 31.2%. The authors concluded that even slow short-term postmeal walking could reduce the blood glucose response to a high carbohydrate meal (Nygaard et al, 2009). Additionally, a recent study in individuals with IFG (blood glucose: 105-125mg/dL) found that 15-minute postmeal walks were significantly more effective at improving 24-hour glycemic control than 45-minutes of sustained morning or evening walking (DiPietro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%